Examining need for uniqueness in emerging markets. Issue 1 (18th October 2017) - Sharma, Dheeraj; Verma, Varsha; Sharma, Subhash
Abstract : Purpose: The purpose of this paper is to conduct a five-country study of consumers' need for uniqueness (CNFU) and examine its research and practical implications. Most studies examining CNFU have used single country or US-based samples. To promote cross-cultural research, the authors test the cross-cultural reliability and validity of the CNFU scale using data from the USA, a developed economy, Brazil, India, Thailand, and Mexico, all emerging economies. Design/methodology/approach: The original CNFU scale was developed in the USA. Therefore, to cross-validate the scale, data were collected from consumers in the USA, Brazil, India, Thailand, and Mexico as these countries demonstrate important socio-economic and cultural differences. The scale was tested using confirmatory factor analysis. Findings: The scale was estimated and validated in all five countries and the analysis reveals that the CNFU scale has sound psychometric properties. Further, the authors find that CNFU is a cross-cultural phenomenon that has a significant impact on market mavenism (MM), and this relationship is moderated by usage variety (UV). Research limitations/implications: The results indicate generality of all the scale items, and demonstrate that CNFU is a cross-cultural phenomenon. Greater nomological validity of the CNFU construct could be established by investigating its relationship with more constructs. Originality/value: The authors provide empirical evidence on the cross-cultural validity of the CNFU scale; examine its effect on MM; and role of UV on the relationship between CNFU and MM.